Evaluation of human attitudes and factors conducive to promoting human–lion coexistence in the Greater Gir landscape, India. Issue 4 (24th July 2021) - Meena, Venkataraman; Johnson, Paul J.; Zimmermann, Alexandra; Montgomery, Robert A.; Macdonald, David W.
Abstract: Coexistence of people and large carnivores depends on a complex combination of factors that vary geographically. Both the number and range of the Asiatic lion Panthera leo leo in the Greater Gir landscape, India, has increased since the 1990s. The challenge has been managing the success of conservation, with a particular focus on the spillover population ranging extensively in human-dominated landscapes. To understand the factors conducive to lion survival in this landscape, we undertook an interview-based survey. Overall, people expressed positive, tolerant attitudes towards lions. There was a distinct contrast between people's liking for lions (76.9% of respondents) compared to leopards (27.7%) in spite of greater depredation of livestock by lions (82.6%) than by leopards (17.4%). Younger people and respondents having greater awareness regarding lions expressed positive attitudes. Although community discussions on lions had a positive effect, there was no evidence that land-holding, management interventions, personal encounters with lions, or association of lions with religion affected attitudes. Respondents who had experienced livestock depredation tended to express negative attitudes. Respondents with positive attitudes towards lions favoured non-interventionist strategies for managing lions in the village areas. We advocate consideration of varied factors influencing tolerance of wildlife in conservation planning. We emphasize that site-specific human–wildlife conflict issues such as crop-foraging by wild ungulates and variation in attitudes towards different species should also be considered. Specifically, improved livestock management, motivation of local youth and their participation in awareness campaigns could all further strengthen the prevalent positive attitudes towards lions.